The Relationship Between Inclination To Change, Self-Efficacy And Resilience Among Drug Addicts In Kajang Prison - Norulhuda Bin Mat Rozei
Statistics show that there is an increase in the number of prisoners in all prison institutions in Malaysia which causes overcrowding. Based on most research findings, the number of prisoners involved in drug abuse cases in prison is approximately 60 percent of the total number of inmates, which is approximately 70,000 people. This situation is compounded by the increase in the rate of recidivism over the past 5 years, which requires research from various aspects. Therefore, this study was conducted on prisoners involved in drug abuse in one of the overcrowded prisons. This study was conducted to examine the level and relationship between the inclination to change, self-efficacy and the level of resilience among drug addicts in Kajang Prison, Selangor. The study sample consisted of 306 prisoners serving their sentence in Kajang Prison. Respondents were selected through simple sampling based on the list of drug offenders in the prison. Three instruments were used in this research, namely the Resilience Scale (RS 25) from Gail M. Wagnild and Heather M. Young (1993) which was translated into Malay by Amalia Madihie, Sidek Mohd Noah, Maznah Baba, & Wan Marzuki Wan Jaafar ( 2011). Meanwhile, the University of Rhode Island Change Assessment Scale Assessment Scale (URICA) was introduced by DiClemente and Hughes (1990) and was translated into Malay by a group of local researchers using the back translation technique. The last instrument used was the General Self-Efficacy Scale by Matthias Jerusalem and Ralf Schwarzer (1992) which was translated into Malay by Siti Zubaidah Hussin (2017). The results of the study found that almost 40 percent of respondents were still at the Pre-contemplation stage despite having followed a drug rehabilitation program. In addition, the results of the descriptive analysis show that most respondents have a low level of self-efficacy but at the same time most respondents have a high level of self-efficacy. Meanwhile, the findings of the study show that there is a positive relationship between the inclination to change, self-efficacy and resilience. The implications of this study help to understand the relationship between the level of resilience, inclination to change and self-efficacy. Further studies are encouraged to explore other aspects that may be able to influence the level of resilience and the inclination to change in all categories of prisoners as an effort to help detention institutions at the treatment level